CAV-1 Overexpression Exacerbates the Manifestation in EPAC-1-Induced Chronic Postsurgical Pain in Rats. (31st July 2022) - Hua, Qian; Shen, Shiren; Qin, Yibin; Cao, Su
Abstract : Purpose . Caveolae (CAV) are an invaginated microcapsule with the shape of Ω on the surface of the cell membrane. Caveolin-1 (CAV-1) is involved in neuropathic pain, and adenosine monophosphate (AMP)-exchange protein directly activated by cAMP1 (EPAC-1) is a potential therapeutic target for chronic pain. However, whether EPAC-1 promotes chronic postsurgical pain (CPSP) through CAV-1 has not been reported. Here, we aim to investigate the underlying mechanism of CAV in CPSP. Methods . All the rats were divided into 9 groups, including the Naive group, Sham group, skin/muscle incision and retraction (SMIR) group, SMIR + CAV-1 siRNA group, SMIR + control siRNA group, SMIR (7 days)+Saline group, SMIR (7 days)+CE3F4 group, 8-PCPT group, and Saline group. The CPSP rat model was established after SMIR. A mechanical withdrawal threshold (MWT) was recorded to evaluate the animal's behavior. Western blotting and immunofluorescent were performed to detect the protein expression levels of EPAC-1 and P-CAV-1. Results . EPAC-1 and CAV-1 were both overexpressed after operation, particularly in astrocytes, microglia, and neurons of spinal marrow (all P < 0.05 ). Interestingly, CAV-1 siRNA can partly reverse the SMIR-induced hypersensitivity, but there was no effect on EPAC-1. Besides, EPAC-1 blockage partly reversed the SMIR-induced hypersensitivity and CAV-1 overexpression, and EPAC-1 activation promoted CAV-1 overexpression and hypersensitivity in normal rats (all P < 0.05 ). Conclusion . CAV-1 mediates the functional coupling of microglia, astrocytes, and neurons, and thus EPAC-1/CAV-1 plays an important role in CPSP exacerbation.